Inventory management performance of essential medicines in public health facilities of Jimma Zone, Southwest Ethiopia. - Azmeraw Bekele; Bekele Boche; Yeniewa Kerie Anagaw; Wondim Ayenew; Minichil Chanie Worku; Derso Teju Geremew; Tefera Minwagaw; Eneyew Melkamu; Alem Endeshaw Woldeyohanins; Bereket Bahiru Tefera; Mengistu Duguma (PLOS Global Public Health)
The inventory management of essential medicines is a crucial aspect of health care delivery, particularly in resource-limited settings. Access to these medicines must be ensured to meet the health needs of the population, demanding effective control of their inflow, outflow, and stock levels. Poor inventory management can lead to significant disruption in the supply chain, ultimately affecting patient care and safety. The aim of this study was to assess inventory Management Performance of Essential Medicines in Public Health Facilities of Jimma Zone, Southwest Ethiopia.A facility-based descriptive cross-sectional mixed-method study was conducted using an observational checklist, semi-structured and structured questionnaires, and triangulation. Twenty public health facilities were randomly included in the study. The quantitative data were coded and analyzed using SPSS version 20. The qualitative data were analyzed using thematic analysis techniques. Out of 20 health facilities, 14 (70%) experienced stock out of 8 (66.6%) essential medicines at least once, and all health facilities experienced emergency orders of varying terms within the previous six months. The result indicated a range of reasons for stock outs of essential medicines, including insufficient medicine supply 11 (55%), stock out at re-supply point 8 (40%), drug expiration 7 (35%), and order modifications at the replenishment point 6 (30%). The mean accuracy of bin card records was 188(78.3%), whereas the mean accuracy of Report and Resupply Form reports was 87.37% with a mean discrepancy of 0.13. Of all completed Report and Resupply Form reports, 56 (93.3%) were sent on time to suppliers. Essential medicines' inventory management performance was inadequate, characterized by prolonged stock outs, frequent emergency orders, and the need to improve storage conditions. Infrastructure-related problems, data management issues, insufficient human resource development, and the inability to integrate digital technology into the inventory management system were the key challenges identified.